PERTAUTAN ANTARA READER, TEXT, DAN AUTHOR DALAM MEMAHAMI NASH - Imam Nurhakim (MAGHZA, 2017)
In the process of understanding the religious text, the reader, text, and author are the three elements that each other are inseparable and / or interrelated. Separating the three can lead to an attitude of authoritarianism in understanding the meaning of texts. The attitude of authoritarianism is an act of arbitrariness in understanding the meaning of texts so it is not uncommon to assume the correct understanding.To avoid such authoritarianism, according to Khaled, negotiations between the three (reader, text, and author) should be established, so that each does not dominate each other in the process of determining the meaning of texts. In other words, the determination of meaning comes from a complex, interactive, dynamic and dialectical process between the three elements (text, author, and the reader). In addition, to stem, prevent and refrain, groups, and religious organizations from authoritarianism in determining the meaning of religious texts, Khaled also proposed five precepts: honesty, self-control, sincerity, whole, and rationality.